Pembimbingan Generasi Alpa Tentang Moderasi Beragama Dalam Perspektif Iman Kristen Di Tk Kasih Ibu Rimba Belian - Anjeli, Martha; Hia, Yeremia (Universitas Pahlawan Tuanku Tambusai, 2025)
Guidance for the Alpha Generation, specifically the children of Kasih Ibu Kindergarten, was conducted to provide balanced spiritual preparation in line with the rapid development of technology today. The main issue faced by the children of Kasih Ibu Kindergarten is the lack of early understanding of the values of religious moderation, balanced with the strengthening of Christian faith. Therefore, this activity serves as a solution and a responsibility for the mentors within this community. The methods employed include direct observation, storytelling, illustrations, and the use of teaching aids in every activity. The outcomes of this guidance program include the creation of an educational environment rooted in Christian spirituality and the development of Alpha Generation children into spiritually prepared individuals with character aligned with Christian faith.